2018
DOI: 10.1021/acs.joc.8b00605
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I)-Catalyzed N–O Bond Formation through Vinyl Nitrene Mediated Pathway under Mild Conditions

Abstract: Copper(I)-catalyzed N-O bond formation reactions through vinyl nitrene-mediated pathway were described. The reactions of N-alkoxylbenzamides and 2 H-azirines afforded α-amino oxime ethers in good to excellent yields at room temperature, which involved the cleavage of C-N and N-O bonds and the construction of new N-O and C-N bonds. It offers an efficient, regio- and stereoselective synthetic route for α-amino oxime ethers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Our previous study showed that the reaction of N ‐alkoxylbenzamides and 2 H ‐azirines could give α‐amino oxime esters in good yields in the presence of 10 mol% of CuI at room temperature . However, under the same conditions, the reaction of N ‐(pivaloyloxy)benzamide 1a and 3‐phenyl‐2 H ‐azirine 2a did not occur, and no any product was found (Table , entry 1).…”
Section: Resultsmentioning
confidence: 95%
“…Our previous study showed that the reaction of N ‐alkoxylbenzamides and 2 H ‐azirines could give α‐amino oxime esters in good yields in the presence of 10 mol% of CuI at room temperature . However, under the same conditions, the reaction of N ‐(pivaloyloxy)benzamide 1a and 3‐phenyl‐2 H ‐azirine 2a did not occur, and no any product was found (Table , entry 1).…”
Section: Resultsmentioning
confidence: 95%
“…As a prominent example, nitrene can be applied as a critical reactive intermediate for the synthesis of valuable N-containing molecules, which is mainly generated by the photolysis of various precursors. , However, the direct photolysis of nitrene precursors requires very harsh short-wavelength irradiation, which leads to poor functional group tolerance and competitive photodecomposition processes that diminish the reaction yield. The strategy of indirect excitation with the help of visible-light photocatalysts, for example, polypyridyl complexes of ruthenium or iridium, was used to overcome this problem. In 2011, Liu and co-workers first reported that a nitrene radical anion can be generated by one-electron reduction of the aryl azide, in which [Ru­(bpy) 3 ] 2+ was employed as the photocatalyst .…”
mentioning
confidence: 99%